1968
DOI: 10.1136/jech.22.3.119
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in pregnancy, maternal blood pressure, pregnancy outcome, baby weight and growth, and other related factors. A prospective study.

Abstract: In an interesting paper Campbell (1936), while welcoming the studies that were being concentrated on improving maternity care, drew attention to what he called "a more subtle and sinister condition", the "excessive smoking" which, during the previous two decades, had "clutched the young women of this country (America) in a manner resembling the invasion of an epidemic working in virgin soil". His paper, which was based on the conviction of his own observations, included his review of the literature and in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2
3

Year Published

1971
1971
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
(24 reference statements)
3
13
2
3
Order By: Relevance
“…The symmetrical reduction in size at birth in infants of smoking mothers suggests that this growth inhibition was present from early fetal development. Earlier and smaller studies have debated whether any size deficit persists into childhood (14,15,20). In our study, infants of smoking mothers showed complete compensatory postnatal catch-up growth in weight, and there was no significant remaining height deficit compared with other infants, however, it is still possible that deficits in bone mineral density and susceptibility to respiratory disease persist (14,20).…”
Section: Discussioncontrasting
confidence: 40%
“…The symmetrical reduction in size at birth in infants of smoking mothers suggests that this growth inhibition was present from early fetal development. Earlier and smaller studies have debated whether any size deficit persists into childhood (14,15,20). In our study, infants of smoking mothers showed complete compensatory postnatal catch-up growth in weight, and there was no significant remaining height deficit compared with other infants, however, it is still possible that deficits in bone mineral density and susceptibility to respiratory disease persist (14,20).…”
Section: Discussioncontrasting
confidence: 40%
“…Quando se considera o ambiente extrauterino, onde não há influência direta do hábito de fumar materno sobre a criança, observa-se que ao final do primeiro ano de vida também não houve diferença significativa entre as médias de peso e altura dos filhos de fumantes e não-fumantes (Tabela 14), confirmando os estudos de Russel e col. 20 .…”
Section: Resultsunclassified
“…Haworth e col. 12 constataram que obesidade materna e fumo agem independentemente, e o excesso de peso materno não protege o feto contra o crescimento retardado resultante do fumo, pois nem o crescimento fetal retardado nas fumantes, nem o crescimento fetal aumentado nas obesas era explicado baseado na energia ingerida através da dieta. Russel e col. 20 afirmam que com um ano de idade, filhos de fumantes e não-fumantes pesam quase igual.…”
unclassified
“…However, maternal, paternal and environmental exposure to smoking are all associated with increased incidence of spontaneous abortion 2. Moreover, patients with a BMI>25 kg/m2 have significantly higher odds of spontaneous abortion 3 4. The lack of consideration of these covariates makes the findings less credible.…”
Section: Commentarymentioning
confidence: 99%